Out of the Darkness and into the Light? Development Effects of Rural Electrification - Burlig, Fiona; Preonas, Louis (Journal of Political Economy, 2024)
Nearly 1 billion people still lack electricity access. Developing countries are investing billions of dollars in “last-mile” electrification, although evidence on its economic impacts is mixed. We estimate the development effects of rural electrification in the context of India’s national electrification program, RGGVY (Rajiv Gandhi Grameen Vidyutikaran Yojana), which reached over 400,000 villages. Using regression-discontinuity and difference-in-differences designs, we estimate that RGGVY meaningfully expanded electricity access. However, the program generated limited economic impacts after 3–5 years. Scaling our intent-to-treat estimates using instrumental variables, we find that “full electrification” reduces welfare in small villages but has a 33% internal rate of return in large villages.